Associations of anxiety and depression with sexual health among infertility patients: a systematic review - Changmin Niu; Yuxin Gao; Qiulian Xu; Fan Yang; Shikun Ma; Nuo Shen; Wenxuan Zhu; Yidi Kong; Lu Chen; Guiqin Wang (Frontiers in Psychology, 2026)
Purpose This study aims to systematically review the associations between anxiety, depression, and the sexual health of patients with infertility, providing a theoretical foundation for reproductive health professionals to develop targeted interventions. Methods A comprehensive literature search was conducted in four English databases (Cochrane Library, EMBASE, Web of Science, and PubMed) and two Chinese databases (CNKI and Wan Fang) from inception to December 31, 2025. Studies were selected following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the quality of the included studies was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Case-Control Studies and the Joanna Briggs Institute Checklist for Analytical Cross-Sectional Studies, as appropriate. All included studies were observational. A meta-analysis was not performed because of substantial heterogeneity in the characteristics of the included studies. Results A total of 21 studies ( n = 6,837 participants) were included, with sample sizes ranging from 50 to 1,468. The findings indicated that anxiety and depression were associated with poorer sexual health among patients with infertility. In women with infertility, higher levels of anxiety and depression were associated with lower libido and sexual arousal, greater difficulties with lubrication and orgasm, and more sexual pain. In men with infertility, anxiety and depression were associated with lower libido, greater difficulty experiencing orgasm, premature ejaculation, and poorer erectile function. Anxiety and depression were also associated with poorer intimacy and communication between partners, including lower perceived security and self-esteem. Conclusion These findings support consideration of psychological and sexual health assessments as components of routine infertility care. Family and partner support may also be considered within comprehensive care; however, its effects on physical, psychological, relationship, and quality-of-life outcomes require evaluation in prospective or interventional studies.